Analysis of Higher Order Thinking Skills (HOTS) in Online Learning by English Teacher - Salihah, Nabila Maratus; Prayudha S, Joko (Journal of Language Intelligence and Culture, 2023)
HOTS is a skill that is needed in the 21st century. This skill requires students to be able to think creatively and think critically in facing future challenges so teachers must be able to teach students through asking questions that demand HOTS skills, but during pandemic covid 19 face-to-face learning has shifted to online learning which makes teachers have to be able to change HOTS learning be an online mode. This study aims to analyze the questions and task given by the teacher during HOTS-based online learning to students. The method used in this research is qualitative by using a descriptive approach. Data is obtained through documentation by analyzing the content of the questions. The data were analyzed through three stages, namely data reduction, data display and data conclusion. The results of the study show that the application of HOTS in learning has a significant impact on providing students' critical reasoning and creativity abilities. In addition, during online learning the teacher provides a number of questions related to HOTS which are at C4, C5 and C6 levels so that students are expected to have better abilities during English learning.